A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific - Vourey, Elodie; Dupoux, Cyndie; Harold, Antony Scott (Zootaxa, 2017)
A new species of marine hatchetfish, Polyipnus laruei sp. nov., is described based on one specimen collected off New Caledonia, in the Western South Pacific. This species is distinguished from the thirty-three known species of Polyipnus by the unique presence of only one OVB photophore. The new species is placed in the P. spinosus species group, characterized by the presence of minute spines on the ventral PV photophore scales and an external multispinate posttemporal process.